Optimum HPLC Conditions for Determination of Dibucaine HCL, Fluocortolone Pivalate and Fluocortolone Caproate by Using Experimental Design - Aşçı, Bürge; Koç, Mesut (Current Pharmaceutical Analysis, 2019)
Introduction: This paper presents the development and validation of a novel, fast, sensitive and accurate high performance liquid chromatography (HPLC) method for the simultaneous quantitative determination of dibucaine HCl, fluocortolone pivalate and fluocortolone caproate in pharmaceutical preparations. Experiment: Development of the chromatographic method was based on an experimental design approach. A five-level-three-factor central composite design requiring 20 experiments in this optimization study was performed in order to evaluate the effects of three independent variances including mobile phase ratio, flow rate and amount of acid in the mobile phase. Conclusion: The optimum composition for mobile phase was found as a methanol:water:acetic acid mixture at 71.6 : 26.4 : 2 (v/v/v) ratio and optimum separation was acquired by isocratic elution with a flow rate of 1.3 mL/min. The analytes were detected using a UV detector at 240 nm. The developed method was validated in terms of linearity, precision, accuracy, limit of detection/quantitation and solution stability and successfully applied to the determination of dibucaine HCl, fluocortolone pivalate and fluocortolone caproate in pharmaceutical topical formulations such as suppositories and ointments.
Keywords: fluocortolone caproate